Proposta de instrumento de pesquisa para verificar aspectos de sustentabilidade do transporte rodoviário de cargas das organizações - Endo, Gustavo Yuho (2016)
The aim of this study is to present a research instrument to verify the economic, environmental and social aspects of cargo road transportation. The methodology was divided into two stages: (1) quantitative approach, in which the descriptive analysis of the variables was performed and the independence or chi-square test was performed; (2) a qualitative approach, in which a research tool was developed to verify the economic, environmental and social aspects of organizations. The results obtained from the quantitative approach showed that there are significant relationships between the variable 'being associated' with the variables: level of schooling; Position held in the company; Use of software to optimize routes; Knowledge of Brazilian Law 13,103 of 2015 and; Have an Integrated Management System. In the qualitative approach, the limitations that the leaders of the companies have in relation to the concept of sustainability were identified. With regard to competitiveness in road freight transport, five or six carriers that dominate the agribusiness segment in the zones Cascavel/PR Brazil were identified. With the application of the questionnaire it was possible to know how the organizations deal with aspects related to sustainability. Finally, the documentary research identified the alignment between the subjects discussed in the interview with the company manager Beta. In relation to the company Gama, we identified some points that occurred in the company and that were not mentioned by the research participant, such as the accomplishment of training for its employees. Based on the information obtained from the three data collection methods, opportunities for improvement in the economic, environmental and social aspects of the companies participating in the research were identified and, from this, proposals for interventions were suggested for organizations, aiming at the maintenance and / or the development of economic, environmental and social aspects.